Concept Art Design For A Game Titled Satrio Piningit - Heazler , Emmanuel; Septian Rachman, Vicky (CV TOPAZART, 2024)
The Jayabaya prophecy is one of the historical relics in Indonesia. Is a book that contains prophecies about the island of Java written in 1743 where the predictions in this book are quite confusing because they have predictions that can be said to be accurate with events in the future of this country of Indonesia. The design of this concept art aims to produce a concept picture of the game that is inspired by the contents of this Jayabaya Prophecy. Concept art book as a media presentation for the audience to provide the initial process of game development from the concept of characters, environments and assets to be used. With this concept art book, the author hopes that readers can get to know the characters in this game better and can also provide knowledge about one historical relic, especially in Indonesia.